Komunikat Zjazdowy . no. 33, 1981 - NSZZ "Solidarność" Zarząd Regionalny Ziemi Łódzkiej, [ed. K. Osada et al.] (ZR Ziemi Łódzkiej NSZZ "Solidarność", 1981)
Creation and circulation: Published more than once a day during the two rounds of the First National Congress of Delegates of Solidarity